2018
DOI: 10.3390/molecules23081982
|View full text |Cite
|
Sign up to set email alerts
|

New Chromones from a Marine-Derived Fungus, Arthrinium sp., and Their Biological Activity

Abstract: Five new chromone derivatives, arthones A–E (1–5), together with eight known biogenetically related cometabolites (6–13), were isolated from a deep-sea-derived fungus Arthrinium sp. UJNMF0008. Their structures were assigned by detailed analyses of spectroscopic data, while the absolute configurations of 1 and 5 were established by electronic circular dichroism (ECD) calculations and that of 2 was determined by modified Mosher ester method. Compounds 3 and 8 exhibited potent antioxidant property with DPPH and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Filamentous fungi produce a wide range of secondary metabolites, and many polyphenolic compounds have been reported to exhibit high radical-scavenging abilities against ROS and free radicals [25]. In the case of marine Arthrinium spp., arthone C and 2,3,4,6,8-pentahydroxy-1-methylxanthone were reported as antioxidants [17]. Our ABTS assay results imply that marine-derived Arthrinium spp.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Filamentous fungi produce a wide range of secondary metabolites, and many polyphenolic compounds have been reported to exhibit high radical-scavenging abilities against ROS and free radicals [25]. In the case of marine Arthrinium spp., arthone C and 2,3,4,6,8-pentahydroxy-1-methylxanthone were reported as antioxidants [17]. Our ABTS assay results imply that marine-derived Arthrinium spp.…”
Section: Resultsmentioning
confidence: 57%
“…They have been discovered to produce natural compounds such as arthrinone, arthrichitin, terpestacin, (1 R ,2 S ,3a S ,8a R )-3a,6-dimethyl-1-(propan-2-yl)-1,2,3,3a,4,7,8,8a-octahydroazulene-1,2-diol (CAF-603), norlichexanthone, myrocins, libertellenones, spiroarthrinols, and griseofulvin derivatives [12,13,14,15]. However, a limited number of bioactive compounds were reported: arthpyrones F–I and apiosporamide (antibacterial) [16]; arthrinins A–D (antitumoral and antiproliferative) [13]; decarboxyhydroxycitrinone, myrocin A, libertellenone C, and cytochalasin E (antiangiogenic); arthone C and 2,3,4,6,8-pentahydroxy-1-methylxanthone (antioxidant) [17]; and cytochalasin K and 10-phenyl-[12]-cytochalasin Z 16 (cytotoxic) [18]. In this regard, it was suggested that marine Arthrinium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpropanoids contain many chemical structure types, such as chromone, coumarin, flavone and lignin, which possess various biological activities including antioxidant, cytotoxic, antimicrobial, and enzyme inhibitory activities. For example, arthone C, a chromone derivative isolated from a deep-sea-derived fungus Arthrinium sp., exhibited potent antioxidant activity (Bao et al 2018). Two tetracyclic coumarin derivatives and two coumarin dimers isolated from the marine-derived fungus Eurotium rubrum showed significant tyrosinase inhibitory activity (Kamauchi et al 2018).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…UJNMF0008) came to our attention during the initial chemical profiling and antimicrobial assays. A subsequent chemical investigation into the ethanol extract of this fungus afforded a series of antibacterial pyridone alkaloids [8] and antiradical chromones [9] . Among them, a known alkaloid named apiosporamide exhibited moderate growth inhibition against two OS cells (U2OS and MG63), and a preliminary mechanism study was also performed, since there had no relevant work reported in the literature [10] .…”
Section: Introductionmentioning
confidence: 99%